Administration Oral Misoprostol after Radical Hysterectomy Due to Cervical Cancer in the Early Stage Decrease Urinary Retention Incident: Pemberian Misoprostol Per Oral Pasca Histerektomi Radikal Pada Karsinoma Serviks Stadium Awal Untuk Menurunkan Insiden Retensio Urine - Rajuddin rajuddin; Lutfi N. Nugroho; hasanuddin hasanuddin (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: to determine the effect of oral Misoprostol after Radical Hysterectomy in the early stage Cervical Cancer to reduce the incidence of urinary retention.Methods: The study was conducted with a prospective cohort method, randomized control trial and double blind to the patients with early stage cervical cancer who performed Radical Hysterectomy in Dr. Zainoel Abidin hospital, Banda Aceh. There are 34 research subjects who had agreed to participate in the study. The research subject divided into 2 groups. The first group who received Misoprostol orally as the intervention group and the other group that received placebo as the control group.Results: The incidence of urinary retention after Radical Hysterectomy in Dr. Zainoel Abidin hospital, Banda Aceh, decreased significantly in the intervention group compared to the control group (P 0,049). In the intervention group Misoprostol reduce residual urine. Ability to void spontaneously and urine volume were increase. The duration of catheterization and length of hospital stay for the patients were shorter.Conclusion: Administration of Misoprostol orally reduce the incidence of urinary retention after Radical Hysterectomy. Oral Misoprostol can be recommended as an additional procedure to reduce urinary retention.Keywords: cervical cancer, misoprostol , radical hysterectomy, urinary retention. Abstrak Tujuan: untuk mengetahui pengaruh pemberian Misoprostol per oral pasca operasi Histerektomi Radikal pada pasien Karsinoma Serviks stadium awal terhadap insidensi retensio urin.Metode: Penelitian dilakukan dengan metode kohort prospektif, randomized control trial dan double blind, pada pasien karsinoma serviks stadium awal yang dilakukan Histerektomi Radikal di RS dr. Zainoel Abidin, Banda Aceh. Terdapat 34 pasien yang telah menyetujui mengikuti penelitian, yang dibagi ke dalam 2 kelompok yaitu kelompok yang mendapat Misoprostol tablet per oral sebagai kelompok perlakuan dan kelompok yang mendapat plasebo sebagai kelompok kontrol. Residu urin pada kedua kelompok diukur dan faktor-faktor lain yang terkait dilakukan pendataan untuk dilakukan analisis. Hasil: Kejadian retensio urin pasca Histerektomi Radikal di RS dr. Zainoel Abidin, Banda Aceh, menurun secara bermakna pada kelompok perlakuan dibandingkan kelompok kontrol (P0,049). Pada kelompok perlakuan Misoprostol menurunkan residu urin.Peningkatan kemampuan berkemih spontan dan volume urin .lama pemakaian kateter transuretra dan lama perawatan menjadi lebih singkat.Kesimpulan: Pemberian Misoprostol per oral mengurangi insiden retensio urin pasca Histerektomi Radikal. Saran : Misoprostol per oral dapat direkomendasikan sebagai prosedur tambahan untuk mengurangi retensio urin.Kata kunci: karsinoma serviks, histerektomi radikal, misoprostol, retensio urin